MATH101 April 2010
• Q1 (a) • Q1 (b) • Q1 (c) • Q1 (d) • Q1 (e) • Q1 (f) • Q2 (a) • Q2 (b) • Q2 (c) • Q3 (a) • Q3 (b) • Q3 (c) • Q3 (d) • Q4 • Q5 (a) • Q5 (b) • Q5 (c) • Q6 • Q7 • Q8 • Q9 •
Make sure you understand the problem fully: What is the question asking you to do? Are there specific conditions or constraints that you should take note of? How will you know if your answer is correct from your work only? Can you rephrase the question in your own words in a way that makes sense to you?

If you are stuck, check the hint below. Consider it for a while. Does it give you a new idea on how to approach the problem? If so, try it!

Hint

We can consider $x$ as a constant inside the integral

Checking a solution serves two purposes: helping you if, after having used the hint, you still are stuck on the problem; or if you have solved the problem and would like to check your work.
 If you are stuck on a problem: Read the solution slowly and as soon as you feel you could finish the problem on your own, hide it and work on the problem. Come back later to the solution if you are stuck or if you want to check your work.
 If you want to check your work: Don't only focus on the answer, problems are mostly marked for the work you do, make sure you understand all the steps that were required to complete the problem and see if you made mistakes or forgot some aspects. Your goal is to check that your mental process was correct, not only the result.

Solution

Found a typo? Is this solution unclear? Let us know here. Please rate my easiness! It's quick and helps everyone guide their studies.
First we solve the integral considering $x$ as a constant:
${\begin{aligned}g(x)&=\int _{0}^{1}(xe^{t}t)^{2}dt\\&=\int _{0}^{1}(x^{2}e^{2t}2xe^{t}t+t^{2})dt\\&=x^{2}\int _{0}^{1}e^{2t}dt2x\int _{0}^{1}e^{t}tdt+\int _{0}^{1}t^{2}dt\\\end{aligned}}$
The first integral in the sum is
$\int _{0}^{1}e^{2t}dt={\frac {1}{2}}(e^{2}e^{0})={\frac {1}{2}}(e^{2}1)$
Now we solve $\int _{0}^{1}e^{t}tdt$ by parts letting $u=t$ and $dv=e^{t}dt$ so that $du=dt$ and $v=e^{t}$. Hence
${\begin{aligned}\int _{0}^{1}e^{t}tdt&=te^{t}{\big }_{0}^{1}\int _{0}^{1}e^{t}dt\\&=(e0)(e1)=1\end{aligned}}$
The last integral in the sum is:
$\int _{0}^{1}t^{2}dt={\frac {1}{3}}(1^{3}0^{3})={\frac {1}{3}}$
So
$g(x)={\frac {x^{2}}{2}}(e^{2}1)2x+{\frac {1}{3}}$
The derivative is directly computed to be:
$g'(x)=x(e^{2}1)2$
Which is zero at $x={\frac {2}{e^{2}1}}$.
To make sure it is a minimum we use the second derivative test. The second derivative is:
$g''(x)=e^{2}1$
Which is always positive (Remember that $e>2$). This means $x={\frac {2}{e^{2}1}}$ is the minimum for $g$. Plugging in this value gives
${\begin{aligned}g\left({\frac {2}{e^{2}1}}\right)&=\left({\frac {2}{e^{2}1}}\right)^{2}{\frac {e^{2}1}{2}}2\left({\frac {2}{e^{2}1}}\right)+{\frac {1}{3}}\\&=\left({\frac {4}{(e^{2}1)^{2}}}\right){\frac {e^{2}1}{2}}{\frac {4}{e^{2}1}}+{\frac {1}{3}}\\&={\frac {2}{e^{2}1}}{\frac {4}{e^{2}1}}+{\frac {1}{3}}\\&={\frac {2}{e^{2}1}}+{\frac {1}{3}}\\&={\frac {6+e^{2}+1}{3(e^{2}1)}}\\&={\frac {e^{2}7}{3(e^{2}1)}}\end{aligned}}$

Click here for similar questions
MER QGH flag, MER QGQ flag, MER QGS flag, MER RT flag, MER Tag Integration by parts, MER Tag Optimization, Pages using DynamicPageList3 parser function, Pages using DynamicPageList3 parser tag

Math Learning Centre
 A space to study math together.
 Free math graduate and undergraduate TA support.
 Mon  Fri: 12 pm  5 pm in LSK 301&302 and 5 pm  7 pm online.
Private tutor
